(untitled) - Hamlyn ([London], 1999)
This text identifies those scientific breakthroughs that triggered fundamental change in human society. From man's discovery of the fire to splitting the atom, the printing press to the microchip, all of the technological advances that helped alter our world-view have been catalogued here. There are also feature biographies of the inventors, scientists and thinkers whose insights and curiosities helped humanity understand - and master - a little more of the world around it. The text is complemented with illustrations that enhance the story of progress and development told here.
Keywords: Science,Khoa học; History,Lịch sử